Adaptation and validation of silhouette scales for Brazilian children Adaptação e validação de escalas de silhuetas para crianças brasileiras - Ferrari E.P. (2018)
© Edições Desafio Singular.The aim of the present study was to adapt and test the construct validity and reliability of the “Children's ABSTRACT Figure Rating Scale” for Brazilian children. The aim of the present study was to adapt and test the construct validity and reliability of the Children's Figure Rating Scale for Brazilian children. The sample consisted of 235 children, 120 boys and 115 girls, with a mean age of 8.8 (± 1.1) years. Besides the scale, it was performed body mass and height to calculate the body mass index. The data were analysed in the Statistical Package for the Social Sciences, version 20.0, using the Spearman correlation, Wilcoxon Test and the Intraclass correlation coefficient, because the data did not present normal distribution according to the Kolmogorov Smirnov test. It was found a positive correlation between the body mass index and the real image for boys (r= 0.42; p= 0.01) and girls (r= 0.34; p= 0.01). The reliability was confirmed by the intraclass correlation coefficient, presenting values above 0.70 (p= 0.001) for both, boys and girls. It was concluded that the scale tested has good psychometric qualities, being configured as a viable option of body image evaluation for Brazilian children.